A evolução do conhecimento de construtibilidade - Abreu, João Paulo Maciel de; Marchiori, Fernanda Fernandes; Haito, Ricardo Juan José Oviedo (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
In civil construction there is a constant search for improvement. Among the ways to achieve it, the concept of constructability stands out. Constructability can be understood as a characteristic of a building or construction project to be easily performed. Since 1962, in Emmerson Report, this concept is growing and involving different areas of construction research. Notwithstanding, there is no consensus about the meaning of this concept, that can be associated to terms such as constructability, buildability, among others, with similar constructs but different scopes in construction life-cycle. The aim of this paper is to show the evolution of constructability knowledge in researches conducted in Brazil and other countries, specially USA, UK, Singapore and Hong Kong. To reach this aim, a bibliometric integrative review was carried out in international databases, including journals and event proceedings, and Brazilian thesis repositories. Three hundred forty-three researches mentioned the terms “constructability” or “buildability” as well its equivalent “construtibilidade”. As a result, it was observed the consolidation of this concept in 2000’s, and the emergence of new ways and tools related to constructability analysis such as indicators systems or analysis using BIM 4D; contributing to the discussion about how to put the constructability concept into practice.